The Psychometric Properties of the Norwegian version of Ages and Stages Questionnaires(ASQ) - Martinussen, Monica; Valla, Lisbeth (PsykTestBarn, 2013)
Description: The Ages & Stages Questionnaires (ASQ) were developed in the 80’s in the USA as a developmental screening tool for babies and young children (Squires, Bricker & Potter, 1997). The set of questionnaires was translated to Norwegian in 2001-2002 by Harald Janson, Beathe Enoksen, and Kristin Furuholmen at the Department of Psychology, University of Oslo. There are different versions of the questionnaire (a total of 19) for different age groups from 4 to 60 months. The Norwegian version, including the manual, may be purchased at www.r-bup.no. The test includes a total of 30 questions grouped into six subscales and a total score. It takes 10 – 20 minutes for parents to complete the questionnaire. Relevant education and training is required for professionals in order to use the test. The ASQ may be used for clinical and research purposes. Literature search: The systematic literature search resulted in 24 articles of which six met the inclusion criteria and included in addition to the test manual. The included studies reported the results from four independent studies. The search for Swedish and Danish studies resulted in one article examining test validity. Psychometrics: The included studies reported mean scores, alpha values, and test-retest reliability. Median alpha value for the total score was > .80 and test-retest reliability was >.70. Norwegian norms are available, but for some age groups based on relatively small samples. Conclusion: The reliability of the total score was good, but unsatisfactory for some of the subscales. There are Norwegian norms based on a sample from the general population with suggested cut-off values. The test validity has only to some extent been examined based on Norwegian or Scandinavian samples.